Attachment Anxiety and Attachment Avoidance: Members' Attachment Fit with Their Group and Group Relationships. Issue 2 (3rd April 2017) - Kivlighan, Dennis M.; Lo Coco, Gianluca; Gullo, Salvatore; Pazzagli, Chiara; Mazzeschi, Claudia
ABSTRACT: We compared each individual group member's attachment fit with the attachment of the other group members. Participants were 201 members of 20 therapy groups who sought treatment because they were overweight or obese. Group members completed the Attachment Style Questionnaire before commencing treatment and the Group Questionnaire at three points during group treatment. Multilevel polynomial regression followed by response surface analysis was used to examine how the attachment anxiety and avoidance of the individual group member and the aggregated attachment anxiety and avoidance of the group members were related to individual group members' perceptions of the positive bonding, positive working relationships, and negative relationships in the group. The findings suggested that attachment heterogeneity in group is related to the perception of members' stronger bonding relationships and lower negative relationships. In addition, positive bonding can be increased when a patient high in attachment avoidance is added to a group whose patients are low in attachment avoidance; however, group members reported weaker negative relationships when their attachment anxiety or avoidance became increasingly higher or lower than other group members' attachment anxiety or avoidance.